2016
DOI: 10.1039/c6nr05055g
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin conjugated nontoxic carbon dots for doxorubicin delivery to target pediatric brain tumor cells

Abstract: Among various cancers, pediatric brain tumors represent the most common cancer type in children and the second most common cause of cancer related deaths. Anticancer drugs and therapies, such as doxorubicin (Dox), have severe side effects on patients during chemotherapy, especially for children as their bodies are still under development. These side effects are believed to be due to the lack of a delivery system with high efficacy and targeting selectivity, resulting in serious damages of normal cells. To impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(130 citation statements)
references
References 28 publications
4
126
0
Order By: Relevance
“…The addition of C‐dots has been reported to increase mechanical strength, cell adhesion, proliferation, and osteogenic differentiation . Unlike GO or CNTs, most C‐dots could be synthesized from essentially any carbon‐containing sources, such as carbon powders, low‐molecular‐weight organic compounds, biomacromolecules, as well as food residues, thus it is possible to construct C‐dots based BTE scaffolds from economically affordable and renewable resources. For example, Gogoi et al fabricated a composite consisting of C‐dots, HA, and polyurethane through a one‐pot hydrothermal approach; notably, the synthesis of HA and C‐dots both utilized green, renewable bio‐based precursors: calcined eggshell as calcium source, and aqueous extract of C. esculenta corm as carbon source (Figure 16B).…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…The addition of C‐dots has been reported to increase mechanical strength, cell adhesion, proliferation, and osteogenic differentiation . Unlike GO or CNTs, most C‐dots could be synthesized from essentially any carbon‐containing sources, such as carbon powders, low‐molecular‐weight organic compounds, biomacromolecules, as well as food residues, thus it is possible to construct C‐dots based BTE scaffolds from economically affordable and renewable resources. For example, Gogoi et al fabricated a composite consisting of C‐dots, HA, and polyurethane through a one‐pot hydrothermal approach; notably, the synthesis of HA and C‐dots both utilized green, renewable bio‐based precursors: calcined eggshell as calcium source, and aqueous extract of C. esculenta corm as carbon source (Figure 16B).…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…Carbon dots (CDots) have attracted extensive attention in the biomedical field due to their unique features, e. g., excitation‐dependent multicolor emission, favorable biocompatibility, good cell membrane permeability, nontoxicity, high water solubility and fluorescence stability . The various functional groups on their surface allow flexible surface modification of CDots to carry several therapeutic agents simultaneously, offering possibility for CDots to be excellent drug nanocarrier with the ability of targeted drug delivery, bioimaging and real‐time monitoring of drug distribution ,,. Folic acid and PEG have been covalently conjugated on CDots for the delivery of doxorubicin (DOX), wherein the former helps to facilitate targeted drug delivery and the latter to enhance fluorescence intensity .…”
Section: Introductionmentioning
confidence: 99%
“…As the therapeutic mechanism of DOX involves DNA damage inside the nucleus induced by DOX, thus nuclear localization signal peptide was covalently conjugated to CDots for targeted delivery of DOX into the internuclear region to improve the therapeutic efficacy ,. A recent study reported the targeted delivery of DOX into pediatric brain tumors by using a CDots‐transferrin‐DOX covalent conjugate . Nevertheless, in most of the CDots‐based nanocarriers for DOX delivery, DOX was simply loaded on the surface of CDots through covalent bonding or nonspecific π–π stacking interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In our continuous efforts to develop C-dots based bioimaging and drug delivery systems, 18, 26, 27 we recently reported that delivery of a particular class of C-dots into the heart or abdominal cavity of zebrafish larvae resulted in the deposition of these C-dots into calcified bones with high affinity and specificity. 18 However, it is unknown whether the high specificity and affinity presented is unique to the type of C-dots prepared in our lab, or it might be a general property for C-dots.…”
Section: Introductionmentioning
confidence: 99%